Multi-Objective Taguchi Optimization of Electrospinning Parameters for the Development of Poly-(vinyl alcohol)/Waste Wooden Utensil Nanocellulose/Phycocyanin Electrospun Fibers - Vergel De Dios, Tabitha P.; Luares, Mia A.; Arboleda, Will; Calibara, Myiesha Dane C.; Estrellado, John Ray C. (Future Science / FSH-PH Publications, 2025)
The lack of widespread commercial repurposing and recycling of waste wooden utensils contribute to pollution and toxic waste in the environment. This study aims to develop a sustainable method of repurposing waste wooden utensils into mechanically-robust electrospun fibers. Waste wooden utensil nanocellulose (WUNC) was produced using delignification, bleaching, and hydrolysis. Polymer mixtures consisting of 10% poly-vinyl alcohol (PVA), WUNC, and the pigment-protein complex phycocyanin (PC) were prepared for electrospinning following the Taguchi robust optimization design. Three parameters, namely WUNC addition (0.1, 0.2, 0.3 g./100 g), PC addition (0.1, 0.2, 0.3 g./100 g), and electrospinning voltage (25, 27.5, 30 kV), were varied to optimize loading capacity and tensile strength. Results showed WUNC addition of 0.2 g./100 g., PC addition of 0.3 g./100 g., and voltage of 25 kV optimal for loading capacity, with PC addition having the highest contribution at 44.54%. WUNC addition of 0.3 g./100 g., PC addition of 0.1 g./100 g., and voltage of 30 kV optimized tensile strength, with WUNC addition having the highest contribution at 57.99%. Produced WUNC resulted in a nanocellulose yield of approximately 16.81% with FTIR spectra revealing the removal of lignin and hemicellulose and increase of cellulose crystallinity. FTIR spectra for the electrospun fibers indicate successful integration of all components in the electrospun fibers. SEM analyses confirmed the creation of electrospun fibers within the nanosize range. Results confirmed the viability to extract nanocellulose and synthesize fibers from waste wooden utensils for enhancement of electrospun mats quality for biomedical applications, and offer new knowledge on wood-based nanomaterials.